Review of PPIUCD at tertiary care centre in Southern Rajasthan - Nirmala Sharma (Manipal College of Medical Sciences, Pokhara, 2021)
Background: This study was conducted to observe the acceptance rate and safety for PPIUCD as PPIUCD was used as contraceptive method under family welfare program in this institute.